The Most Common Cardiovascular, Orthopedic, and Neurological Problems in the Elderly and Nursing Care - Pirushi, Rudina; Imeraj, Zamira; Veseli, Denisa; Bilali, Valbona (Open Access Macedonian Journal of Medical Sciences, 2022)
AIM: Health problems of the elderly in addition to purely medical constitute a complex and quite acute social, economic, psychological, and spiritual problem, which are growing unstoppably everywhere in the world. The main purpose of this study is to assess the general health of the elderly, to identify the most common pathologies, and to describe the role and responsibilities of the nurse in the elderly with cardiovascular, neurological, and orthopedic diseases, in all patients in geriatric clinics. METHODS: The method used during this study was conducted through a questionnaire of the elderly in geriatric centers. The paper includes data on patients during the period April–June, 2020. RESULTS: Data were observed on 300 elderly persons of whom 100 persons or 33% were female and 200 persons or 67% were male. The mean age of patients was 90 ± 65 years. These elderly people were given information about living conditions, social problems, diseases they had, etc. The most common pathologies of these elderly people studied were cardiovascular problems 25%, orthopedic problems 31%, and neurological problems 43%. We see that women are more predisposed to cardiovascular problems in 66% of cases compared to men in 34% of cases; most predisposed to orthopedic problems are again women in 55% of cases compared to men in 45% of cases and more predisposed to neurological problems are men in 60% of cases and women in 40% of cases, it is significant (p < 0.001). CONCLUSIONS: From the above data, it is noticed that almost all the elderly have a concomitant disease. The role of the nurse should be to focus on the daily monitoring of the patient’s condition, to identify in time the possible risks, and to explain to the patient how to take the therapy, how long to take this therapy, what may be the side effects and how medications should be combined.